APLIKASI TIGA DOSIS PUPUK FOSFOR PADA EMPAT VARIETAS SORGUM (Sorghum bicolor (L.) Moench) DALAM MENINGKATKAN KOMPONEN HASIL DAN MUTU FISIOLOGIS BENIH - Zuhry, Elza; ', Marlina; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research was increase yield components and physiological seed quality and determined the proper dose of phosphorus fertilizer on four sorghum varieties. This research has been conducted  in Field Experiment and the plant breeding laboratory, Faculty of Agriculture, University of Riau, from April 2014 to October 2014. The research conducted by using  randomized  block  design  (RBD) which arranged factorial with 2 factors and 3 replications. The first factor was a fertilizer dose of SP-36, namely: 45 kg SP-36,  90 kg SP-36 kg and 135 kg SP-36 / ha. The second factor was the sorghum varieties those Kawali, Numbu, Pahat and Mandau. The mean separation of analysis of variance was tested using Duncans multiple range test at 5%. Parameters those observed: seed weight / panicle, weight of 1000 seeds, seed weight/m2, seed moisture content, germination test, first count test, rate of germination, seedling dry weight, plumule growth and radicel test. The results showed that phosphorus fertilizer increases the grain weight / panicle, weight of 1000 seeds and seed weight/m2.The phosphorus fertilizer application of 90 kg/ ha showed the best effect on the variety Pahat (8,50 ton/ha) and Mandau (8,7 ton/ha). The Phosphorus fertilizer application increases the physiological seed quality on all parameters except the water content.The phosphorus fertilizer application 135 kg/ha gave the best quality of the seed physiology of Mandau and Numbu. Keywords : Sorghum bicolor, phophorus, yield component, physiological seed quality